2016
DOI: 10.1002/mc.22491
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 promotes growth and liver metastasis of colorectal cancer in mice by remodeling the tumor microenvironment and inducing angiogenesis

Abstract: Liver metastasis is the major cause of death from colorectal cancer (CRC). Understanding its mechanisms is necessary for timely diagnosis and development of effective therapies. Interleukin-33 (IL-33) is an IL-1 cytokine family member that uniquely functions as a cytokine and nuclear factor. It is released by necrotic epithelial cells and activated innate immune cells, functioning as an alarmin or an early danger signal. Its role in invoking type 2 immune response has been established; however, it has contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 53 publications
2
109
1
Order By: Relevance
“…Interleukin‐33 could recruit IL‐1R‐associated kinase 1 and 4 to the receptor complex in cytoplasmic region of ST2 by binding to the IL‐33 receptor, which triggers numerous signaling downstream, including NF‐κB, that might lead to inflammation . Activated NF‐κB enhances the expression of various proteins that could promote metastasis . In our results, after knockdown of IL‐33, the level of CCL2 was decreased when the NF‐κB pathway was inhibited.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Interleukin‐33 could recruit IL‐1R‐associated kinase 1 and 4 to the receptor complex in cytoplasmic region of ST2 by binding to the IL‐33 receptor, which triggers numerous signaling downstream, including NF‐κB, that might lead to inflammation . Activated NF‐κB enhances the expression of various proteins that could promote metastasis . In our results, after knockdown of IL‐33, the level of CCL2 was decreased when the NF‐κB pathway was inhibited.…”
Section: Discussionmentioning
confidence: 48%
“…It was reported that IL‐33 could be secreted by necrotic epithelial cells, and then bind to its cognate ST2 receptor, thus activating mitogen‐related protein kinase and NF‐κB . Results from previous studies indicated that IL‐33 has a proinflammatory function and is considered as a “danger” signal .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL33 transcript levels were found to be higher in stage I–III CRC compared to adjacent normal colonic tissue. However, IL33 expression was lower in stage IV CRC than in stage I–III intestinal tumors (84). In contrast, another study reports progressively increasing levels of IL33 and IL1RL1 transcript from low to high grade and stage of human CRC (85).…”
Section: Main Review Textmentioning
confidence: 99%
“…Experiments using bone marrow (BM) chimeric mice indicated that IL-33/ST2 signaling was engaged on both the radio-resistant and the radio-sensitive compartment (83). In a different model of CRC, syngeneic MC-38 colon carcinoma cells injected into the cecum of recipient mice showed enhanced growth and liver metastasis when overexpressing IL-33 (84). …”
Section: Main Review Textmentioning
confidence: 99%
See 1 more Smart Citation